Metadata and Quality in Digital Repositories and Libraries from 1995 to 2015: A Literature Analysis and Classification. Issue 3 (3rd July 2017) - Palavitsinis, Nikolaos; Manouselis, Nikos; Sánchez-Alonso, Salvador
ABSTRACT: The purpose of this article is to study a broad set of journal papers related to metadata and quality in digital repositories and libraries, and to provide a quantitative analysis of the relevant research. It also aims at identifying open issues and future directions for research. A detailed search was carried out in relevant journals of information science, computer science, and library science; mainly, that allowed us to identify an extensive corpora of relevant work. The identified papers were classified based on an existing framework and a statistical analysis was carried out on the main classifications used within the framework. The analysis of the 702 papers identified, led to a series of statements for the field examined, focusing on the type of research carried out, the research methods deployed, and the research claims made. In addition, the papers were classified based on their target audiences, disciplines, as well as institutional and geographical origins. The article identifies areas in the literature that have not been addressed, as well as areas for future research. It also provides a clear image of the areas already researched, analyzing scientific literature that covers 20 years of repository/library deployment. This article makes an original contribution for researchers, practitioners, and managers of digital repositories and libraries alike as it provides a set of specific recommendations for the metadata and quality in digital repositories and libraries research agenda, along with a thorough analysis and classification of the research carried out so far.